2023
DOI: 10.3390/nu15092124
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Glucans of Cereals: Functional and Technological Properties

Abstract: β-glucans are a polymeric dietary fiber characterized by β-(1,3) and β-(1,4) glycosidic bonds between glucose monomers. They are often used as thickeners, stabilizers, and fat substitutes in foods. The functional and technological quality of β-glucans is attributed to their origin/source, molecular weight, and structural properties. In particular, physical treatments such as drying, cooking, freezing, and refrigeration influence their molecular, morphological, and rheological characteristics. In addition to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 68 publications
1
16
0
1
Order By: Relevance
“…This possibility is not a surprise, as previous studies have shown that ETEC K88 variants could recognise N-acetylhexosamine β-linked to a Gal residue and β1-linked galactosyl residues in intestinal glycoconjugate receptors [ 30 , 31 ]. It is also worth noting that the differences in the structures or types of glycosidic bonds and branches of β-glucans in the tested cereals and mushrooms may involve anti-adhesive processes [ 9 , 16 , 17 ]. Furthermore, regarding the β-glucans from shiitake and jelly ear, although they both consist of (1→3)-β-D-glucopyranoside units and β-(1→6)-d-glucosyl residues, their varied structures probably caused different anti-adhesive effects between EST and EJE [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility is not a surprise, as previous studies have shown that ETEC K88 variants could recognise N-acetylhexosamine β-linked to a Gal residue and β1-linked galactosyl residues in intestinal glycoconjugate receptors [ 30 , 31 ]. It is also worth noting that the differences in the structures or types of glycosidic bonds and branches of β-glucans in the tested cereals and mushrooms may involve anti-adhesive processes [ 9 , 16 , 17 ]. Furthermore, regarding the β-glucans from shiitake and jelly ear, although they both consist of (1→3)-β-D-glucopyranoside units and β-(1→6)-d-glucosyl residues, their varied structures probably caused different anti-adhesive effects between EST and EJE [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heteropolysaccharides from the S. cerevisiae cell wall, which mainly contain glucan and mannan, have also been shown to reduce E. coli adhesiveness in vitro and in vivo [ 12 ]. These findings have encouraged the search for functional foods, especially those rich in β-glucans, such as highland barley, shiitake and jelly ear, although the physicochemical properties of these compounds may vary between different food sources [ 13 , 14 , 15 , 16 , 17 ]. Additionally, several studies have explored the potential biological activity of these foods, particularly their influence on the composition of the intestinal microbiota, due to their high glucan content [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Darüber hinaus gilt es Herstellungs-und Verarbeitungsprozesse von Ballaststoffsupplementen zu beachten. Diese können bei manchen löslichen Ballaststoffen zu Veränderungen der molekularen Struktur, des Polymerisationsgrads und dadurch letztendlich zur Veränderung/Verminderung der physiologischen Wirkung führen [29]. β-Glucane z.…”
Section: Diskussionunclassified
“…β-glucan, which has attracted attention in recent years through its potential contributions to health, is also used as an additive in many foods due to its beneficial effects as well as its gelling and thickening features [1]. Using β-glucan as a food additive in a variety of food industries, including breakfast cereals, prebiotic sausage formulations, sports nutrition products, dairy products like yoghurt, H. Demir DOI: 10.4236/as.2023.1412112 1733 Agricultural Sciences bakery products like cookies, bread, cakes, and ready-to-eat snacks, beverages, salad dressings, and fat substitutes, has a noticeable potential in the near future [2].…”
Section: Introductionmentioning
confidence: 99%